Resiliensi penyintas Covid-19: apa peran dari dukungan sosial? - Mahendra, Marcellinus Aditya Agung; Apsari, Florentina Yuni (Fakultas Psikologi Universitas Hang Tuah, 2024)
Abstract. This study aimed to determine the relationship between social support and resilience in early adult survivors of Covid-19 in Surabaya. The research method used was the quantitative method. The participants of this study amounted to 110, aged 18-40 years, were COVID-19 survivors, and lived in Surabaya. Participants were selected using a purposive sampling technique. The research instruments used were the social support scale and the resilience scale. Data were analyzed with Kendall's Tau-B non-parametric correlation test. The results showed a relationship between social support and resilience in early adult survivors of COVID-19 in Surabaya with a correlation coefficient of 0.654. The study's results can be used as the basis for intervention design.